2000
DOI: 10.1097/00003246-200006000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Diaspirin-crosslinked hemoglobin reduces mortality of severe hemorrhagic shock in pigs with critical coronary stenosis

Abstract: Fluid resuscitation with 10% DCLHb solution completely reverses hemorrhagic shock-induced subendocardial ischemia and hypoxia in the presence of compromised coronary circulation and thereby prevents early death after resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
1
34
1
Order By: Relevance
“…In addition, the myocardial blood flow values as well as the ratio of sub-endocardial to subepicardial blood flow were found in good agreement with the data obtained in previous studies [12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the myocardial blood flow values as well as the ratio of sub-endocardial to subepicardial blood flow were found in good agreement with the data obtained in previous studies [12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 90%
“…Parts of the results of this extensive study have already been published [6,16]. Briefly, it was demonstrated that all animals treated with DCLHb survived the observation period after completion of fluid resuscitation, whereas 5 out of 10 HSA-treated animals died of acute LV failure within 20 min after termination of resuscitation.…”
Section: Resultsmentioning
confidence: 96%
“…appendix). The myocardial perfusion was assessed by the radioactive microsphere technique which has already been described in detail elsewhere [6,15,16].…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In experimental studies on severe shock, resuscitation using HBOCs consistently stabilized the hemodynamics and tissue oxygenation. 27 The potential uses for HBOCs in the future include cases of shock, organ ischemia, red blood cell incompatibility, acute lung injury, transplant organ preservation, sickle cell anemia, tumor therapy and air embolism. 6 The potential advantages offered by oxygen carriers include universal compatibility, one to three years of shelf life compared with 42 days for blood cells, the ability to be produced in large quantities, a manufacturing process that can reduce the risk of infectious agents, reduced dependence on donor blood supplies and an alternative for patients who will not accept transfusions of red blood cells, such as Jehovah's Witnesses.…”
Section: Final Considerationsmentioning
confidence: 99%